(untitled) (Global Journal of Management and Business Research, 2018)
Currently, enterprises shape the economic engine of any country or region. Certainly, Puebla municipality#x2019;s case in Mexico is not the exception, considering that more than 95% of the enterprises settled in Puebla are micro most of them being familiar businesses. These types of businesses find trouble with the creation and functioning of the enterprise, due to the fact that they do not count with any funding source. That is the reason why it is a matter of interest identify the different funding sources used by this businesses. In order to achieve the research#x2019;s main purpose, a research#x2019;s instrument was created and applied to managers or owners of the familiar businesses in Puebla. The information gathered showed that most of them started the business with their own capital, by the time they had collected the enough amount of money. Likewise, it was found that the main funding sources are family or friends#x2019; money, bank credits are less requested. To conclude, results showed that the most common funding sources used by familiar businesses in Puebla are family members, friends or even their own capital. Unfortunately, the Mexican Bank System does not really support micro entrepreneurs.